The Reflective Practice Writing Bicycle: A Reflective Analysis Tool for Engaged Learning - Priestley, Edmund (Religious studies and theology, 2019)
Traditional university education has focused on academic learning, which is followed by a graduate’s attempts to apply this learning to various career-related pursuits. Experiential learning turns this focus on its head - at least partially. Instead of learning preceding praxis, learning now follows praxis. In this latter model, much of the post-praxis learning is focused and achieved via reflective analysis of experience - also called reflective practice - through written reflection. Reflective Practice Writing (RPW), also called Reflective Practice Journaling, is much more than traditional journaling. For reflective practice to effectively facilitate the learning process for students, RPW requires students to deeply probe and explore their experience to realize maximum learning. A guide or a "tool" to assist this process is useful and, I argue, required but, in too many cases, is either inadequate or not provided at all. This paper provides and describes such a reflective practice writing tool, which has been imagined as a bicycle - with a "front wheel" and a "back wheel" of spokes or questions. A reflective practice writing tool cannot, however, simply be developed on its own; it must be tied to a teaching and learning philosophy which has student learning integration and, ultimately, student transformation as its goal. The Reflective Practice Writing Bicycle is based precisely on such a teaching/learning philosophy, which is integrated into The RPW Bicycle tool itself.